Control of diabetic hyperglycaemia and insulin resistance through TSC22D4 - Üstünel, Bilgen Ekim; Friedrich, Kilian; Sticht, Carsten; Gretz, Norbert; Fleming, Thomas; Nawroth, Peter Paul; Stremmel, Wolfgang (Nature Communications, 2016)
TSC22D4 regulates hepatic lipoprotein production, but has so far mainly been studied in the context of cancer cachexia. Here, the authors show TSC22D4 inhibition improves insulin sensitivity in several mouse models of diabetes, which they attribute at least in part to the induction of secreted LCN13.